2020
DOI: 10.1038/s41598-020-77373-8
|View full text |Cite
|
Sign up to set email alerts
|

Concerted cell and in vivo screen for pancreatic ductal adenocarcinoma (PDA) chemotherapeutics

Abstract: PDA is a major cause of US cancer-related deaths. Oncogenic Kras presents in 90% of human PDAs. Kras mutations occur early in pre-neoplastic lesions but are insufficient to cause PDA. Other contributing factors early in disease progression include chronic pancreatitis, alterations in epigenetic regulators, and tumor suppressor gene mutation. GPCRs activate heterotrimeric G-proteins that stimulate intracellular calcium and oncogenic Kras signaling, thereby promoting pancreatitis and progression to PDA. By contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Expression of RGS16-green fluorescent protein (GFP), which inhibits Gi/ q-coupled GPCRs, negatively regulates pancreatic ductal adenocarcinoma (PDA) progression and can be used for rapid preclinical in vivo validation of novel chemotherapeutic agents targeting early lesions in patients at high risk for successful resection or progression to PDA. RGS16-GFP has recently been reported in caerulein-induced acinar cell dedifferentiation, early tumor and throughout PDA progression (Layeghi-Ghalehsoukhteh et al, 2020) (Ocal et al, 2015). This suggests that RGS16 may be used as a prognostic marker for pancreatic cancer and PDA.…”
Section: Role Of Rgs16 In Tumorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Expression of RGS16-green fluorescent protein (GFP), which inhibits Gi/ q-coupled GPCRs, negatively regulates pancreatic ductal adenocarcinoma (PDA) progression and can be used for rapid preclinical in vivo validation of novel chemotherapeutic agents targeting early lesions in patients at high risk for successful resection or progression to PDA. RGS16-GFP has recently been reported in caerulein-induced acinar cell dedifferentiation, early tumor and throughout PDA progression (Layeghi-Ghalehsoukhteh et al, 2020) (Ocal et al, 2015). This suggests that RGS16 may be used as a prognostic marker for pancreatic cancer and PDA.…”
Section: Role Of Rgs16 In Tumorsmentioning
confidence: 91%
“…Therefore, as a member of the RGS protein family and an important regulatory protein of the GPCR pathway, RGS16 undoubtedly serves a nonnegligible role in tumorigenesis. More specifically, recent studies have found that the RGS16 protein is associated with a variety of cancer types, including breast cancer (Wiechec et al, 2008;Liang et al, 2009;Wiechec et al, 2011;Hoshi et al, 2016), pancreatic cancer (Kim et al, 2010;Carper et al, 2014;Ocal et al, 2015;Zolghadri et al, 2018;Layeghi-Ghalehsoukhteh et al, 2020), colorectal cancer (Buckbinder et al, 1997;Miyoshi et al, 2009), neuroblastoma (Liu et al, 2005;Airoldi et al, 2006), glioma (Huang et al, 2020), chondrosarcoma (Sun et al, 2015), hyper diploid acute lymphoblastic leukemia in children (Davidsson et al, 2007) and other malignant tumors. RGS16 has been studied in breast cancer.…”
Section: Role Of Rgs16 In Tumorsmentioning
confidence: 99%